Physics before and after Einstein - M. Mamone Capria (ed.) (IOS Press, 2005)
It is now a century ago that one of the icons of modern physics published some of the most influential scientific papers of all times. With his work on relativity and quantum theory, Albert Einstein has altered the field of physics forever. It should not come as a surprise that looking back at Einstein's work, one needs to rethink the whole scope of physics, before and after his time. This books aims to provide a perspective on the history of modern physics, spanning from the late 19th century up to today. It is not an encyclopaedic work, but it presents the groundbreaking and sometimes provocative main contributions by Einstein as marking the line between 'old' and 'new' physics, and expands on some of the developments and open issues to which they gave rise. This presentation is not meant as a mere celebration of Einstein's work, but as a critical appraisal which provides accurate historical and conceptual information. The contributing authors all have a reputation for working on themes related to Einstein's work and its consequences. Therefore, the collection of papers gives a good representation of what happened in the 100 years after Einstein's landmark Annalen der Physik articles. All people interested in the field of physics, history of science and epistemology could benefit from this book. An effort has been made to make the book attractive not only to scientists, but also to people with a more basic knowledge of mathematics and physics.